Training on Making Street Light Poles Using Light Steel for the Community of Griya Permata Housing Complex, Handil Bakti Village, Alalak District, Barito Kuala Regency, South Kalimantan Province - Effendie, Faryanto; Khaliq, Abdul; Fakhrurrazi, Fakhrurrazi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Training on making street lighting poles using light steel can be an effective solution in improving the quality of lighting in public areas. Light steel has several advantages, such as lighter weight, resistance to corrosion, and ease of installation compared to conventional materials such as concrete or wood. The implementation of training activities on making street lighting poles using light steel was carried out on Saturday, May 25, 2024 at the Welding and Plumbing Workshop, Banjarmasin State Polytechnic. It is hoped that this training can contribute to community empowerment, where participants can apply the skills they have acquired to open small businesses in the manufacture and installation of lighting poles